Phrases of biblical origin in Polish marketing chrematonymy – the case of contemporary company names (origins, adaptation, functions) - Puda-Blokesz, Magdalena (Papers in Linguistics, 2026)
The article discusses adaptations of multiword lexical items from the Bible in Polish marketing chrematonymy. The subject concerns two methodological research areas – chrematonomastic and phrasematic, since they both deal with proper names of companies, actually one of their parts – firmonyms (brand names) based on biblical phrases. The research material was collected with the use of the search engine of the Biznes.gov.pl portal. We looked at: (I) the genetic status of biblical phrases relocated into usable chrematonymy, (II) the mechanisms of formal adaptation of multiword biblical phrases in the stock of company names, and briefly (III) the most important functions of biblical firmonyms. The research has shown, among other findings, that name creators reach for biblical phrases of various genetic status and subject them to various formal modifications, which may affect the level of the firmonym’s saturation with so-called ‘biblicality’ perceived/ decoded by the recipient. It can also be seen that names based on the Bible do not always serve to identify the industry, but also fulfil other functions, above all they evaluate the referent and their activities.